The Effects of Left Ventricular Assist Device Implantation on Physical Activity, and the Acute and Chronic Physiological Responses to Exercise - Moreno Suárez, Jose Ignacio (Curtin University, 2020)
This PhD thesis found that left ventricular assist devices (LVADs), small pumps implanted into the hearts of people with advanced heart failure, are associated with higher levels of physical activity, improved fitness and better brain blood flow compared with people with advanced heart failure, but without an LVAD. Furthermore, high intensity interval exercise training in people with LVADs was safe and more effective than moderate intensity exercise for further improving fitness.